The Psychology of Leadership: New Perspectives and ResearchThe Psychology of Leadership: New Perspectives and Research, edited by Messick David Kramer Roderick. Mahwah, NJ: Lawrence Erlbaum Associates, 2005. - Locander, William; Luechauer, David (Academy of Management Review, 2005)
The article reviews the book ?The Psychology of Leadership: New Perspectives and Research,? edited by David Messick and Roderick Kramer.